Correlation between the unit cell volume and bulk modulus with the average covalent radii for AI-BIII-CVI2 and AII-BIV-CV2 chalcopyrite compounds - Pérez Kuroki, Ana J.; Cárdenas, K.; Grima Gallardo, P. (Ciencia, 1970)
All the physical properties of a crystal are related to the virtual geometrical lattice and the real atomic basis associated to it. If the geometrical lattice is fixed (all the compounds under study belongs to the same space group), the physical properties, from a compound to another, will differentiate only by the real atomic basis. i.e. the physical properties can be compared as a function of structural parameters as the lattice parameter, bond length, atomic radii, or similar. In this work, we will study compounds that crystallize in the chalcopyrite structure (s.g. I42d) using as structural parameter, the average covalent radii ( ). We will show that a good correlation exists between the unit cell volume (V = a2 c ) and the isothermal bulk modulus (B0) with, for AI-BIII-CVI2 and AII-BIV-CV2. chalcopyrite compounds.